Determination of an Optimum Extraction Time and Its Production Cost of Powdered Extract of Guava (Psidii folium) Leaf - Sukardi, Sukardi; Mulyarto, A. R.; Safera, W. (Jurnal Teknologi Pertanian, 2007)
A randomized block design experiment was performed to determine the optimum extraction time and its production cost for producing a extract powder of guava (Psidii folium) leaf. The extraction process was carried out for 5; 10; 15; 20; 25 and 30 minutes respectively. The extract was then dried and the parameters observed were the yield, the levels of tannin, moisture, pH and the production cost. The results showed that the yield, the characteristics of the powdered extract, as well as the production cost, varied with the extraction time. Based on the regression technique, it was likely that 17.5 minutes was the optimum extraction time. The yield was 2.67 % at 4.42 % moisture and contained 0.3968 g per 5 g (7.936 %) tannin with the pH of 4.32. The production cost was IDR (Indonesian Dollar Rupiah) 875 per 5 g powdered extract.Key word : Extraction time, guava leaf, powdered extract